2022
DOI: 10.1371/journal.pone.0273832
|View full text |Cite
|
Sign up to set email alerts
|

Collagen pre-strain discontinuity at the bone—Cartilage interface

Abstract: The bone-cartilage unit (BCU) is a universal feature in diarthrodial joints, which is mechanically-graded and subjected to shear and compressive strains. Changes in the BCU have been linked to osteoarthritis (OA) progression. Here we report existence of a physiological internal strain gradient (pre-strain) across the BCU at the ultrastructural scale of the extracellular matrix (ECM) constituents, specifically the collagen fibril. We use X-ray scattering that probes changes in the axial periodicity of fibril-le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…With this in mind, our results provide novel insight into the mechanical response of this fundamental tissue unit, considering it as an isolated system. One of the primary reasons for higher fracture strains of the MCFs with increasing mineral content was the higher residual strains in the system caused by presence of these minerals, which is a feature that has also been observed experimentally [67]. Eliminating the residual strain, our simulations showed that the fracture strain actually remained unchanged for different mineral contents.…”
Section: Discussionsupporting
confidence: 70%
“…With this in mind, our results provide novel insight into the mechanical response of this fundamental tissue unit, considering it as an isolated system. One of the primary reasons for higher fracture strains of the MCFs with increasing mineral content was the higher residual strains in the system caused by presence of these minerals, which is a feature that has also been observed experimentally [67]. Eliminating the residual strain, our simulations showed that the fracture strain actually remained unchanged for different mineral contents.…”
Section: Discussionsupporting
confidence: 70%
“…4 G and I. It is well known that COL Ⅱ is associated with chondrocyte proliferation and cartilage phenotype maintenance [ 53 ]. Therefore, the small- and medium-pore regions were beneficial to chondrocyte proliferation and retain their differentiation capacity.…”
Section: Resultsmentioning
confidence: 99%
“…SMAE allows us to efficiently recover physical information of spatially and temporally resolved data. For spatially resolved data, the strain gradient and orientation distribution information related to bone collagen fibers and minerals, which is essential for determining the nanoscale physiological status of bone health (Xi et al, 2018;Badar et al, 2022;Inamdar et al, 2021) but severely deteriorated due to constituent decrease, can be efficiently retrieved under shorter X-ray exposure times. For temporally resolved data, the SNR of an X-ray pattern with 2 s exposure time under SMAE zeroshot mode is comparable to an unoptimized pattern with 120 s exposure time, giving the Beijing Synchrotron Radiation Facility (a first-generation synchrotron light source) the ability to carry out time-resolved PDF experiments at the second timescale without instrumentation upgrades.…”
Section: Discussionmentioning
confidence: 99%